Preparation of Liposome Entrapping Pluchea indica Less. Leaf Extracts for Application in Cosmetic Products - อิสระสุข, ขวัญจิต; ไตรยะสุข, ณัฐพงษ์; ไตรยะสุข, ณัฐพงษ์; พรหมสมบูรณ์, ชลดา; พรหมสมบูรณ์, ชลดา; มีพืชน์, จุฑามาศ; รักษ์ทอง, ลลิตา; อิ่มเสถียร, นิสุฎา; ศรีบุรินทร์, ณัฏฐรัตน์; จันตรี, กัลยาภรณ์; นาคนก, ประดับฟ้า (Journal of Food Health and Bioenvironmental Science, 2017)
This study was aimed to prepare the liposome entrapped extract from leaves of Pluchea indica Less for application in cosmetic products. An extract of dried P.indica leaves was produced by a maceration technique using 95% ethanol. The crude extract was tested for antioxidant activity, according to the DPPH assay. The extract exhibited dose-dependent antioxidant activity with an IC50 value of 0.27±0.002 mg/mL; this extract was compared to positive controls, L-ascorbic acid and butyl hydroxytoluene (BHT). The phenolic and flavonoid contents in P.indica extract were investigated. The phenolic and flavonoid contents were 280.30±10.0 mgGAE/g extract and 542.1±5.71 mgQE/g extract, respectively, determined by the Folin-Ciocaltue assay and the aluminium chloride method, respectively. The tyrosinase inhibitory activity of the extract was assayed by the dopachrome method using tyrosine as a substrate. The results found that the P.indica extract possessed tyrosinase inhibition activity with an IC50 value of 0.0038±0.01 mg/mL compared to kojic acid, used as a positive control. The reverse phase evaporation method was utilized to obtain well-form P.indica extract entrapped liposomes. The prepared liposomes displayed a mean particle size of 445.3±11.3 nm, with a minimum polydispersity index (PDI) of 0.36±0.01. The entrapment efficiency of liposome loading P.indica extract was found to be 63.61± 2.58%, obtained by incorporating Lipoid ® (phospholipid) and cholesterol 2:1 molar ratio. The sum of the findings indicate possible applications for the P.indica extract in skin lightening cosmetic products.